2019
DOI: 10.1111/1365-2656.12994
|View full text |Cite
|
Sign up to set email alerts
|

Costs and drivers of helminth parasite infection in wild female baboons

Abstract: Helminth parasites can have wide‐ranging, detrimental effects on host reproduction and survival. These effects are best documented in humans and domestic animals, while only a few studies in wild mammals have identified both the forces that drive helminth infection risk and their costs to individual fitness. Working in a well‐studied population of wild baboons (Papio cynocephalus) in the Amboseli ecosystem in Kenya, we pursued two goals, to (a) examine the costs of helminth infections in terms of female fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 93 publications
11
46
0
Order By: Relevance
“…Using 31 fecal samples from wild baboons for which we had both parasite data and IgA concentrations (obtained with the in‐house ELISA), we tested the relationship IgA concentrations and two measures of parasitism linked to costs in female baboons: Trichuris trichiura egg counts and parasite richness (i.e., the count of distinct parasite species in the sample). T. trichiura is the most common parasite in our population, occurring in 92.5% of the female fecal samples, and in 96% of the male samples (Akinyi et al, 2019; Habig et al, 2019). Furthermore, previous research in our population has found that both T. trichiura egg counts and parasite richness are associated with reduced fertility (i.e., long interbirth intervals) in female baboons (Akinyi et al, 2019).…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Using 31 fecal samples from wild baboons for which we had both parasite data and IgA concentrations (obtained with the in‐house ELISA), we tested the relationship IgA concentrations and two measures of parasitism linked to costs in female baboons: Trichuris trichiura egg counts and parasite richness (i.e., the count of distinct parasite species in the sample). T. trichiura is the most common parasite in our population, occurring in 92.5% of the female fecal samples, and in 96% of the male samples (Akinyi et al, 2019; Habig et al, 2019). Furthermore, previous research in our population has found that both T. trichiura egg counts and parasite richness are associated with reduced fertility (i.e., long interbirth intervals) in female baboons (Akinyi et al, 2019).…”
Section: Methodsmentioning
confidence: 88%
“…T. trichiura is the most common parasite in our population, occurring in 92.5% of the female fecal samples, and in 96% of the male samples (Akinyi et al, 2019; Habig et al, 2019). Furthermore, previous research in our population has found that both T. trichiura egg counts and parasite richness are associated with reduced fertility (i.e., long interbirth intervals) in female baboons (Akinyi et al, 2019). T. trichiura burdens and parasite richness were estimated by counting parasite eggs in fecal samples via fecal flotation and sedimentation (Bowman, 2014; Gillespie, 2006).…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations